(untitled) (Texas Journal of Engineering and Technology, 2024)
In this article, the effect of the pressing rollers in the stretching mechanisms on yarn breaks during yarn spinning is studied. The mechanical properties of the pressing rollers and how their loading affects the strength and quality of the thread have been studied. In the course of the research, practical recommendations were developed to reduce thread breaks and optimize stretching mechanisms